Performance of Broilers Fed Varying Levels of Palm Kernel Cake - Bello, K.M.; Oyawoye, E.O.; Bogoro, S.E.; Dass, U.D. (International Journal of Poultry Science, 2011)
The high cost of conventional feed ingredients has necessitated the investigation into unconventional readily available feedstuffs such as Palm Kernel Meal (PKM). The study was conducted to determine the effect of using different levels of PKM in broilers chicks diet on performance, cost effectiveness, blood chemistry and carcass characteristics. Two hundred (200) day old Anak 2000 broiler chicks were in a completely randomized design allocated to five dietary treatments (0, 10, 20, 30 and 40% PKM) in four replicates. The birds were fed isonitrogenous and isocaloric diets containing 21% crude protein and 2700 kcal/kgME at the starter phase and 23% CP and 3000 kcal/kgME for the Finisher phase. The result showed that the feed intake and daily weight gain increases significantly (p<0.05) with increase in PKM inclusion up to 30% while the FCR were similar to the control. Performance in terms of daily weight gain and FCR indicated that birds on PKM diet perform equally well as those on the control diets. Similarly, the feed cost/kg weight gains were slightly better on the PKM based diet than the control. The result of the blood biochemical analysis showed there was no significant treatment effect on all the haematological parameters measured, which indicates that PKM does not contain any anti nutritional factor. Similarly, the carcass analysis showed non-significance effect of level of PKM on most of the organs except the heart, gall bladder and back weight. The gall bladder and back weight showed significant (p<0.05) increase with increase in PKM inclusion level while the heart weight was not following any particular pattern. These findings show that PKM can be included at 30% level in the diet of broilers without a negative effect on performance, carcass yield and blood constituents.